A Comprehensive Analysis of Modern Investment Principles: Trends, Challenges, and Investment Implications in the Digital Age - Erlita, Ita; Majid, Nurholis; Ohoiwutun, Y. A. Triana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to examine and analyze recent developments in investment practices and outcomes in the digital era. The main focus includes the impact of financial technology (FinTech) adoption on corporate investment efficiency and allocation, the behavior of retail investors increasingly influenced by social media and online trading platforms, as well as the dynamics of sustainable investment (ESG) and its implications for financial performance. In addition, this study highlights policy aspects and managerial practices that are relevant to the changing landscape of modern investment. Based on a synthesis of literature from the past five years, the findings indicate that digitalization—through the use of FinTech and online platforms—has transformed capital allocation mechanisms while also affecting investor decision-making patterns. Meanwhile, empirical evidence regarding the impact of ESG-based investments on corporate performance remains heterogeneous, indicating the need for more comprehensive data and consistent reporting standards. Thus, this study contributes to a deeper understanding of the trends, challenges, and implications of investment in the digital era.